1984
DOI: 10.1002/ajh.2830160110
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal infarction caused by paroxysmal nocturnal hemoglobinuria

Abstract: A patient with paroxysmal nocturnal hemoglobinuria of 14 years duration presented with severe abdominal pain and fever. On admission, his hematocrit had fallen to 19% from his usual level of approximately 30%, and stools were positive for occult blood. Dilated loops of small bowel with air fluid levels were noted on radiographs, and sonography revealed free intraperitoneal fluid. Several sections of gangrenous jejunum and ileum were resected at exploratory laparotomy, and mesenteric venous thromboses were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This accords well with the observation that these organisms are rarely seen in acute urinary infections, being more commonly implicated in chronic conditions, especially after use of indwelling urinary catheters. 5 The results of this study also suggest that the use of cysteine supplemented agar media has no particular advantage over MacConkey agar for patients from a general practice population presenting with acute urinary tract infections. report the results of our study in which we compared activated partial thromboplastin times (APTTs) and British ratios in 50 patients receiving long term warfarin treatment.…”
Section: Incidence Of Cysteine Dependent Escherichia Cofi In a Generamentioning
confidence: 68%
“…This accords well with the observation that these organisms are rarely seen in acute urinary infections, being more commonly implicated in chronic conditions, especially after use of indwelling urinary catheters. 5 The results of this study also suggest that the use of cysteine supplemented agar media has no particular advantage over MacConkey agar for patients from a general practice population presenting with acute urinary tract infections. report the results of our study in which we compared activated partial thromboplastin times (APTTs) and British ratios in 50 patients receiving long term warfarin treatment.…”
Section: Incidence Of Cysteine Dependent Escherichia Cofi In a Generamentioning
confidence: 68%
“…Recurrent attacks of abdominal pain are common. The possibility that a thrombosis in the portal or mesenteric veins is the cause of the pain must always be taken in consideration (14). Severe abdominal pain dominated the clinical feature of one of our patients.…”
Section: Pnh and Thrombosismentioning
confidence: 86%
“…Since Crosby 5 reported that 54% of patients were found to have hepatic or portal thrombi, there have been four reported cases of intestinal ischemia treated successfully with surgical intervention. 6–10 …”
Section: Discussionmentioning
confidence: 99%